2015
DOI: 10.1016/j.jfluidstructs.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the fluid forces and fluid-elastic instabilities of a clamped–clamped cylinder in turbulent axial flow

Abstract: In this article, the fluid forces and the dynamics of a flexible clamped-clamped cylinder in turbulent axial flow are computed numerically. In the presented numerical model, there is no need to tune parameters for each specific case or to obtain coefficients from experiments. The results are compared with the dynamics measured in experiments available in literature. The specific case studied here consists of a silicone cylinder mounted in axial water flow. Computationally it is found that the cylinder loses st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…Ersdal and Faltinsen [22] showed that the lift coefficient depends closely on the Reynolds number. De Ridder et al [23] reached the same conclusions as Ersdal and Faltinsen [22] and Divaret et al [21] numerically. From the literature, it is difficult to estimate the damping of a structure under axial flow as the range of value for Cn and the dependency on various parameters seems wide.…”
Section: Introductionsupporting
confidence: 54%
“…Ersdal and Faltinsen [22] showed that the lift coefficient depends closely on the Reynolds number. De Ridder et al [23] reached the same conclusions as Ersdal and Faltinsen [22] and Divaret et al [21] numerically. From the literature, it is difficult to estimate the damping of a structure under axial flow as the range of value for Cn and the dependency on various parameters seems wide.…”
Section: Introductionsupporting
confidence: 54%
“…Solitary cylinders display this linear dependency of the viscous force on the angle of attack only if the apparent angle of attack is below 2 degrees (De Ridder et al, 2015;Divaret et al, 2014). At higher angles, the force becomes quadratically dependent on the angle of attack.…”
Section: Non-linear Viscous Forcesmentioning
confidence: 96%
“…At even higher flow velocity (not shown on the graph), the eigenfrequency goes to zero, and the cylinders will buckle. Note that a solitary cylinder behaves similarly (De Ridder et al, 2015;Modarres-Sadeghi et al, 2008).…”
Section: First Mode Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is implemented in the in-house coupling code Tango, which handles the communication between the flow solver and the structural solver. The code Tango has been programmed in C++ and has been validated for a number of different applications (Annerel et al (2014); De Ridder et al (2015Ridder et al ( , 2017), including the simulation of sloshing in a tank where the fluid subproblem was modelled with the VOF technique (Degroote et al (2010)) similar to the method applied in the flow problem presented in this paper. As both solvers are commercial codes and therefore are black-box solvers, the Jacobian of the FSI-system is unknown.…”
Section: Fluid-structure Interactionmentioning
confidence: 99%